Porous bodies of hydroxyapatite produced by a combination of the gel-casting and polymer sponge methods (2016)
ABSTRACT: A combination of gel-casting and polymeric foam infiltration methods is used in this study to prepare porous bodies of hydroxyapatite (HA), to provide a better control over the microstructures of samples. These scaffolds were prepared by impregnating a body of porous polyurethane foam with slurry containing HA powder, and using a percentage of solids between 40% and 50% w/v, and three different types of monomers to provide a better performance. X-Ray Diffraction (XRD), and Fourier Transformed Infrared (FTIR) and Scanning Electron Microscopy (SEM) were employed to evaluate both the powder hydroxyapatite and the scaffolds obtained. In addition, porosity and interconnectivity measurements were taken in accordance with the international norm. Bioactivity was checked using immersion tests in Simulated Body Fluids (SBF). After the sintering process of the porous bodies, the XRD results showed peaks characteristic of a pure and crystalline HA (JCPDS 9-432) as a single phase. SEM images indicate open and interconnected pores inside the material, with pore sizes between 50 and 600 lm. Also, SEM images demonstrate the relatively good bioactivity of the HA scaffolds after immersion in SBF. All results for the porous HA bodies suggest that these materials have great potential for use in tissue engineering.